L'argot dans les chansons des soldats de la Grande guerre - Szkopiński, Łukasz (Linguistica (Ljubljana), 2018)
During the First World War songs played an extremely important role not only for the morale of the soldiers and as a means of political propaganda, but above all as a source of opinion and distraction. The aim of this article is firstly to present some examples of songs from the Great War, to highlight some of their dominant themes and to analyse their linguistic content with a special emphasis on the use of slang. The next part of the article focuses on the definition of the "argot des poilus", that is the military jargon of the First World War soldiers, and on its role in the analysed texts. Several books and dictionaries devoted to this subject were published between 1915 and 1919, a time when everything concerning the soldiers and their experiences on the front, including certain aspects of their jargon, as popularised by the songs, was of special importance to the society of that period. This contributed to an in-depth analysis of military slang and to a greater openness towards slang studies in general. The paper also examines the functions of slang and jargon in the texts in question, and shows that two main types of language transfer were possible in this context. On the one hand, through songs or the press, slang words penetrated into the language behind the frontlines, and on the other hand, there are examples of literary creations that enriched the actual military jargon itself.
Keywords: argo; francoščina; svetovna vojna 1914-1918; vojaške pesmi; vojaško besedišče; vojni besednjak